Characterization of Muscle Spindle Afferents in the Adult Mouse Using an In Vitro Muscle-Nerve Preparation - Wilkinson, Katherine A.; Kloefkorn, Heidi E.; Hochman, Shawn (PLOS ONE, 2012)
We utilized an in vitro adult mouse extensor digitorum longus (EDL) nerve-attached preparation to characterize the responses of muscle spindle afferents to ramp-and-hold stretch and sinusoidal vibratory stimuli. Responses were measured at both room (24°C) and muscle body temperature (34°C). Muscle spindle afferent static firing frequencies increased linearly in response to increasing stretch lengths to accurately encode the magnitude of muscle stretch (tested at 2.5%, 5% and 7.5% of resting length [Lo]). Peak firing frequency increased with ramp speeds (20% Lo/sec, 40% Lo/sec, and 60% Lo/sec). As a population, muscle spindle afferents could entrain 1:1 to sinusoidal vibrations throughout the frequency (10–100 Hz) and amplitude ranges tested (5–100 µm). Most units preferentially entrained to vibration frequencies close to their baseline steady-state firing frequencies. Cooling the muscle to 24°C decreased baseline firing frequency and units correspondingly entrained to slower frequency vibrations. The ramp component of stretch generated dynamic firing responses. These responses and related measures of dynamic sensitivity were not able to categorize units as primary (group Ia) or secondary (group II) even when tested with more extreme length changes (10% Lo). We conclude that the population of spindle afferents combines to encode stretch in a smoothly graded manner over the physiological range of lengths and speeds tested. Overall, spindle afferent response properties were comparable to those seen in other species, supporting subsequent use of the mouse genetic model system for studies on spindle function and dysfunction in an isolated muscle-nerve preparation.